UPAYA MENINGKATKAN KINERJA MANAJERIAL KEPALA SEKOLAH MELALUI PELAKSANAAN SUPERVISI MANAJERIAL PENGAWAS SEKOLAH PADA SMP BINAAN DI KABUPATEN BLITAR SEMESTER 2 TAHUN PELAJARAN 2020/2021 - Winarto, S.Pd. M.Pd I., Kabul (Universitas Islam Balitar, 2021)
The purpose of this study was to determine the improvement of the principal's managerial performance through supervision of 4 fostered junior high schools in Blitar Regency in Semester 2 of the 2020/2021 Academic Year. The research conducted was a school action research in an effort to improve the managerial performance of school principals and was carried out in 4 fostered junior high schools, namely SMP Negeri 1 Panggungrejo, SMP Negeri 2 Panggungrejo, SMP Negeri One Roof Kaligambir and SMP PGRI Panggungrejo which are in the area of the Education Office of Blitar Regency Province. East Java. The research subjects were principals in the 4 junior high schools with a duration of 5 (five) months, from January to May 2021. The results obtained in the initial conditions there were no principals who were declared to have managerial performance in good criteria, in the first cycle increased to 2 principals (50.00%), and in the last cycle to 4 principals (100%). The average score of 50.59 in the Poor criteria increased to 69.74 in the Enough criteria and 90.20 in the Good criteria. Based on the initial conditions, cycle I to cycle II, it can be concluded that there has been an increase in the principal's managerial performance. The results of observations and assessments showed that there was a significant increase in the principal's managerial performance after the coaching activities with managerial supervision were carried out. managerial supervision carried out by school supervisors can improve the managerial performance of school principals in 4 fostered junior high schools in Blitar Regency, so that these results can be used as a reference for improving the managerial quality of principals.